PENGGUNAAN INSTAGRAM SEBAGAI SOCIAL MEDIA MARKETING DALAM MEMBANGUN BRAND AWARENESS PLATBM1912 DI KOTA PEKANBARU - Walid "; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Social media Instagram is one of the social networking applications that are very popular in the community especially among the celebrities and politicians. Business that match Social Media Instagram include entertainment, service, food and beverage, design, and fashion. One of the fashion business that is quite developed in Pekanbaru city is PlatBM1912. The use of social media Instagram is part of marketing communications conducted by PlatBM1912. The purpose of this study is to know how the use of social media instagram as social media marketing in building brand awareness platBM1912 in the city of Pekanbaru.This research uses qualitative research type. Subjects in this study is instagram PlatBM1912 account with the number of informants as many as 5 people. Data collection techniques use obsevation, interview, documentation and internet searching. Data analysis techniques used are interactive models Miles and Huberman. Technique examination of data validity using triangulation technique.The results show that in improving consumer knowledge that is not aware of the brand (Unaware Of Brand), then PlatBM1912 do paid promote, endorsement program, facebook Ads. In the brand recognition stage, PlatBM1912 performs brand recognition to its consumers through Instagram social media is the intensity of sharing photos or video of products owned by Platbm1912 brand to its customers, sharing capture of the photos of customers of PlatBM1912. And have another strategy that is by posting regularly, at least 3 times a day. in doing brand recall to its customers, PlatBM1912 do high intensity by enliven Instagram account. Then in increasing the top of mind on consumers, PlatBM1912 always try to make Instagram as a means of promotion place that aims to build brand awareness of the community, especially the city of Pekanbaru.Keywords:Brand Awareness, Promotion Mix, Social Media Marketing